2015
DOI: 10.1111/isqu.12180
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Democratization

Abstract: Do remittances stabilize autocracies? Remittances—money sent by foreign workers to individuals in their home country—differ from other sources of external non‐tax revenue, such as foreign aid, because they accrue directly to individuals and thus raise the incomes of households. We argue that remittances increase the likelihood of democratic transition by undermining electoral support for autocratic incumbents in party‐based regimes. Remittances therefore make voters less dependent on state transfers. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 98 publications
1
66
0
1
Order By: Relevance
“…Research so far has focused on the impact of remittances on electoral vs. non-electoral political behavior (Careja & Emmenegger, 2012;Germano, 2013;Goodman & Hiskey, 2008;Nyblade & O'Mahony, 2014;O'Mahony, 2013;Pérez-Armendáriz & Crow, 2010;Dionne, Inman & Montinola, 2014), as well as on the impact of remittances on the survival of autocrats and the likelihood of democratization (Ahmed, 2012;Escribà-Folch, Meseguer, & Wright, 2015;Moses, 2011;Pfutze, 2012Pfutze, , 2013. Whether remittances constitute yet another resource curse that may feed government corruption is another subject on the research agenda (Tyburski, 2012(Tyburski, , 2014.…”
Section: Financial Remittances and The Statementioning
confidence: 99%
“…Research so far has focused on the impact of remittances on electoral vs. non-electoral political behavior (Careja & Emmenegger, 2012;Germano, 2013;Goodman & Hiskey, 2008;Nyblade & O'Mahony, 2014;O'Mahony, 2013;Pérez-Armendáriz & Crow, 2010;Dionne, Inman & Montinola, 2014), as well as on the impact of remittances on the survival of autocrats and the likelihood of democratization (Ahmed, 2012;Escribà-Folch, Meseguer, & Wright, 2015;Moses, 2011;Pfutze, 2012Pfutze, , 2013. Whether remittances constitute yet another resource curse that may feed government corruption is another subject on the research agenda (Tyburski, 2012(Tyburski, , 2014.…”
Section: Financial Remittances and The Statementioning
confidence: 99%
“…Migrants are increasingly part of the global supply chain and are consumers of products manufactured in their homeland. At the macro-level, scholars have found that remittances play an important role in shaping a country's exchange rate regime preferences (Singer, 2010) and, under certain conditions, can facilitate a country's transition into democracy by undermining support for autocrats (Escriba-Folch, Meseguer, & Wright, 2015). And, like their ancestors centuries earlier, migrants funnel capital directly back to their families and friends through remittances.…”
mentioning
confidence: 99%
“…It is unclear to what extent migrant and diaspora engagement by democracies and non-democracies differs across the globe. Both regime types have shown they can benefit from financial remittances, and many emerging democracies actively encourage labour migration (Escribà-Folch et al, 2015), as do some authoritarian regimes (Tsourapas, 2015(Tsourapas, , 2018b.…”
Section: Theoretical and Empirical Contributions Of This Special Issuementioning
confidence: 99%